Evidence for the role of Irk2 and Irk5 in ATP and metabolism regulation in Cryptococcus neoformans - Ma, Yuanyuan; Qu, Jianhua; Xu, Mingming; Zhou, Nuoya; Chen, Xiaoya; Han, Yu; Xue, Peng (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionCryptococcus neoformans, a human fungal pathogen, harbors the kinases Irk2 and Irk5, which are classified within the APH phosphotransferase, AGC/YANK protein kinase, and diacylglycerol kinase-like kinase families. Both Irk2 and Irk5 are pivotal for virulence during lung and brain infections. Previous studies have demonstrated that deletion of the IRK5 gene results in a significant reduction in cell wall associated melanin production, a vital virulence factor that facilitates evasion of host immune responses, while deletion of IRK2 does not manifest any notable phenotypic alterations.MethodsTo investigate the impact of IRK2 or IRK5 deletion, we generated targeted deletion mutants for each gene. Following the creation of these mutants, we conducted mass spectrometry analyses to evaluate changes in their proteomic and metabolomic profiles. Moreover, we measured intracellular ATP levels in both the wild-type and mutant strains to assess modifications in ATP synthesis.ResultsMass spectrometry analyses revealed significant alterations in protein and metabolite expression levels in the IRK2 or IRK5 deletion mutant compared to the wild-type strain. Furthermore, the deletion of either IRK2 or IRK5 resulted in notable changes in intracellular ATP levels.ConclusionThis study suggests that the core virulence kinases Irk2 and Irk5 may play roles in regulating ATP levels and metabolic pathways. By elucidating the effects of these kinases on the proteomic and metabolomic profiles of C. neoformans, this research contributes to our understanding of the underlying molecular mechanisms involved in the pathogenesis of this pathogen.